EDUCATION MEDIA IN THE PERSPECTIVE OF ISLAMIC EDUCATION - Imam Tabroni; Ikah Farihatunnisa; Novi Siti Fatimah; Muammira Idris; Rini Purnama Sari (Pusat Riset dan Inovasi Nasional, 2022)
The development of science and technology is increasingly encouraging reform efforts in the use of technological results in the teaching and learning process. One of the results of technology that can be used in the teaching and learning process is educational media. The educational media used must be adapted to the developments and demands of the times. The use of appropriate educational media in the teaching and learning process will facilitate the achievement of learning objectives. The purpose of this paper is to describe that educational media have been known and used in the Islamic education system since the beginning of Islam. The discussion method used is descriptive method. The results of this study are that at the beginning of the spread of Islam, teaching and learning activities were known, at that time educational media already existed and had been applied by the Prophet Muhammad SAW in teaching science and Islamic religious law to his friends. In addition, in the hadith there are several terms used to indicate the use of educational media in learning, such as pictures, pebbles, and fingers. The conclusion of this paper is that educational media will affect whether or not a learning information is complete and on target, as well as affect the final result of the learning process that is carried out. implemented.